Evaluación de un biofertilizante a base de bacillus subtilis + pseudomonas fluorescens en dos variedades mejoradas de trigo (Triticum Aestivum L.), en dos tiempos de aplicación y con el uso de materia orgánica, bajo invernadero en la estación experimental Santa Catalina. - Masabanda Sacatoro, Erika Mishell (2023)
This research study was carried out under the Cereals Program at the Santa Catalina Experimental Station (EESC) of the National Institute of Agricultural Research (INIAP) in Cutuglagua Parish, Mejía Canton, Pichincha Province, Ecuador. The general objective was to evaluate a biofertilizer based on Bacillus subtilis + Pseudomonas fluorescens in two improved varieties of wheat (Triticum aestivum L.), in two application times and with the use of organic matter, under greenhouse. For this purpose, the following was carried out: (1) to evaluate the response of Bacillus subtilis + Pseudomonas fluorescens in the wheat varieties INIAP-Vivar 2010 and INIAP-Imbabura 2014, (2) to identify the optimal application concentration of Bacillus subtilis + Pseudomonas fluorescens in the wheat crop, (3) to establish the application times of Bacillus subtilis + Pseudomonas fluorescens in wheat, (4) to determine the response of Bacillus subtilis + Pseudomonas fluorescens at two levels of organic matter and (5) to determine the interaction between varieties, biofertilizer concentration, application times and organic matter. A Randomized Complete Block Design (RCBD) was established, with factorial arrangement AxBxCxD + 4N (controls), with a total of 28 treatments with 4 repetitions. For data analysis, the Kolmogorov goodness test and the Kruskal Wallis test were performed, generating ANOVA, table of means and figures for the evaluated variables: days to heading, plant height, green matter, dry matter, length of spike, number of grains per spike, grain weight and yield, based on Manual No. 111 of Evaluation and Selection Parameters in Cereals. With the data obtained, it was shown that Bacillus subtilis + Pseudomonas fluorescens concentration 1x1011 CFU, with two application times (Zadoks 0/Inoculation and Zadoks 50) and the use of organic matter (M2) had the best performance with 4444.96 kg ha-1. for wheat variety INIAP-Vivar 2010 and the concentration of 1x1012 CFU, with two application times (Zadoks 0/Inoculation and Zadoks 50) and the use of organic matter (M2) obtained a yield of 4298.51 kg ha-1. in the wheat variety INIAP Imbabura 2014. It was determined that the use of Bacillus subtilis + Pseudomonas fluorescens gave the best response in the wheat yield variables INIAP-Vivar 2010 and INIAP-Imbabura 2014.